Сцинтиляційні матеріали на основі твердих розчинів ZnSxSe₁₋x - Трубаєва, О.Г.; Чайка, М.А.; Галкін, С.M.; Лалаянц, А.І.; Непокупна, Т.А. (Технология и конструирование в электронной аппаратуре, 2018)
Проведено комплексне дослідження процесу отримання мікрокристалічного ZnSxSe₁₋x із суміші порошків ZnS та ZnSe з різним вмістом вихідних компонентів. Проведено комплексное исследование процесса получения образцов микрокристаллического ZnSxSe₁₋x из смеси исходных порошков ZnS и ZnSe с различным содержанием исходных компонентов. Composite materials based on ZnSxSe₁₋x solid solutions are promising materials for gamma and X-ray detectors. However, influence of compositions and particle size on scintillation properties is unclear, which prevents their application. This paper reports on the complex study of microcrystalline ZnSxSe₁₋x powdered scintillations, prepared by solid phase synthesis from ZnS and ZnSe initial compounds. ZnSxSe₁₋x solid solutions were obtained in the range of x from 0.07 to 0.86 and in the following sizes: 200—250, 140—200, 140—80 μm, and less than 80 μm.